Experimental RTM manufacturing analysis of carbon/epoxy composites for aerospace application - Brocks, Thatiane [UNESP]; Shiino, Marcos Yutaka [UNESP]; Cioffi, Maria Odila Hilário [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Caporalli Filho, Angelo [UNESP] (ABM, ABC, ABPol, 2013)
The success of manufacturing composite parts by liquid composite molding processes with RTM depends on tool designs, efficient heat system, a controlled injection pressure, a stabilized vacuum system, besides of a suitable study of the preform lay-up and the resin system choice. This paper reports how to assemble a RTM system in a laboratory scale by specifying heat, injection and vacuum system. The design and mold material were outlined by pointing out its advantages and disadvantages. Four different carbon fiber fabrics were used for testing the RTM system. The injection pressure was analyzed regarding fiber volume content, preform compression and permeability, showing how these factors can affect the process parameters. The glass transition temperature (Tg) around 203 ºC matched with the aimed temperature of the mold which ensured good distribution of the heat throughout the upper and lower mold length. The void volume fraction in a range of 2% confirmed the appropriate RTM system and parameters choice.
Keywords: Resin Transfer Moulding (RTM); woven fabric; non-crimp fabric; process monitoring